Asthma: A Loss of Post-natal Homeostatic Control of Airways Smooth Muscle With Regression Toward a Pre-natal State - Anthracopoulos, Michael B.; Everard, Mark L. (Frontiers in Pediatrics, 2020)
The defining feature of asthma is loss of normal postnatal homeostatic control of airways smooth muscle (ASM). This is the key feature that distinguishes asthma from all other forms of respiratory disease. Failure to focus on impaired ASM homeostasis largely explains our failure to find a cure and contributes to the widespread excessive morbidity associated with the condition despite the presence of effective therapies. The mechanisms responsible for destabilising the normal tight control of ASM and hence airways calibre in postnatal life are unknown but it is clear that atopic inflammation is neither necessary nor sufficient. Loss of homeostasis results in excessive ASM contraction which, in those with poor control, is manifest by variations in airflow resistance over short periods of time. During viral exacerbations, the ability to respond to bronchodilatorsis partially or almost completely lost, resulting in ASM being ‘locked down’ in a contracted state. Corticosteroids appear to restore normal or near normal homeostasis in those with poor control and restore bronchodilator responsiveness during exacerbations. The mechanism of action of corticosteroids is unknown and the assumption that their action is solely due to ‘anti-inflammatory’ effects needs to be challenged. ASM, in evolutionary terms, dates to the earliest land dwelling creatures that required muscle to empty primitive lungs. ASM appears very early in embryonic development and active peristalsis is essential for the formation of the lungs. However, in postnatal life its only role appears to be to maintain airways in a configuration that minimises resistance to airflow and dead space. In health, significant constriction is actively prevented, presumably through classic negative feedback loops. Disruption of this robust homeostatic control can develop at any age and results in asthma. In order to develop a cure, we need to move from our current obsession with immunology and inflammatory pathways to work that will lead to an understanding of the mechanisms that contribute to ASM stability in health and how this is disrupted to cause asthma. This requires a radical change in the focus of most of ‘asthma research’.